Prevention and alleviation of allergic rhinitis by oral administration of Lacticaseibacillus paracasei GOLDGUT-Lpc969 - Zhou, Xiaoli; Song, Xizi; Shu, Ting; Zhang, Silu; Zhang, Zhizhu; Hu, Canying; Pan, Jie; Dai, Xiaoshuang; Hao, Huaijie; Xiao, Guoxun; Wang, Pengfei; Liu, Kai (Frontiers in Immunology, 2024)
Allergic rhinitis (AR) is a widespread upper-airway disorder characterized by inflammation of the nasal passages. It is immunologically mediated via the hypersensitivity type I mechanism, which is primarily elicited by the immunoglobulin E (IgE)-linking allergen-induced imbalance of Th2/Th1 immune response. Due to limited efficacy of current medications, probiotics have received attention for their potential in preventing and ameliorating AR. In this study, a Lacticaseibacillus paracasei strain GOLDGUT-Lpc969 (Lpc969), isolated from feces of healthy adults, had been proved to be effective in preventing AR. The strain significantly attenuated the release of histamine and degranulation in LPS-induced RBL-2H3 cells. While in the OVA-induced AR mice, L. paracasei GOLDGUT-Lpc969 also exhibited significant decrease on the disease indicators such as disease activity index (DAI score), serum IgE, and serum histamine. Treatment with L. paracasei GOLDGUT-Lpc969 led to significant suppression of Th2-related cytokines IL-4, IL-5, IL-6, IL-13 and TNF-α in the serum of mice. Furthermore, a comparison of the genomes of three previously reported AR-effective L. paracasei strains (including GOLDGUT-Lpc969) and one non-effective L. paracasei strain revealed that the gene K03671 may play a key role in alleviating AR symptoms. In conclusion, this study highlights the efficacy of L. paracasei GOLDGUT-Lpc969 in AR prevention through suppressing Th2 immune response and proposes the potential involvement of the functional gene K03671 in ameliorating AR symptoms. Therefore, L. paracasei GOLDGUT-Lpc969 shows promise as a probiotic for preventing AR.